ENVIRONMENTAL POLLUTION: EFFECT ON PEDESTRIANS WHILE WALKING IN URBAN STREET - Onifade, Adepoju; Folasayo, Babatunde; Babatunde , Abimbola (International Journal of Environmental Sciences, 2021)
Purpose: The reason for this study is because of observed difference in environmental condition in Lagos metropolis. The change is witnessed in environmental change arising from air, water and noise pollution mostly from increasing vehicle emissions in the State. This study has been conducted to analyze the environmental effects of pollution on pedestrians. Specific objectives are determine the air quality of the city at most populate headquarters of each of the 20 Local Government Areas of Lagos State, to examine the impact of pollution (air, water and noise) on pedestrians and assess various measures for reducing environmental pollution in the State. Methodology: The use of Thermo scientific MIE pDR-1500 instrument was used to measure air quality index of the selected locations and survey was carried out with well-structured questionnaire to elicit information with the aid of incidental sampling technique on impact of pollution on pedestrians from 177 respondents. Findings: Air Quality Index was shown with histogram chart where six out of 20 Local Government Areas are above the acceptable standard of pollution. There is rising cases of pollution in the State and very few Local governments were within acceptable range. One -Sample T-test showed that air pollution is majorly affecting pedestrians with t-value of 22.226 followed by noise with 19.643 and water with 5.529 respectively. Conclusion and recommendations: The research concluded that, there is need to control the rising cases of pollution in the state and policies to tame air and noise pollution in the state should be adopted. Emission control strategies to be adopted with the existing ones can be in form of restricting hours of movement of vehicles to late at night to avoid human pollutant contact, encourage tree planting and rapid evacuation of environmental waste.